Evaluasi Kinerja Badan Pendapatan Daerah Kota Denpasar Dalam Pemungutan Pajak Bumi Dan Bangunan Perdesaan Perkotaan - Sukma Putri, IGA Anastasia; Noviari, Naniek (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the performance of the Denpasar City Revenue Agency in collecting Rural and Urban Land and Building Taxes. This study uses secondary data with data analysis used in this study is a comparative descriptive analysis related to value for money. Based on the results of the analysis, it can be seen that the performance of the Denpasar City Revenue Agency from the economic aspect is categorized as quite economical by obtaining an average economic ratio of 82%, from the efficient aspect classified as very efficient by obtaining an average efficiency ratio of 2.82 %, and from the aspect of effectiveness classified as very effective category by obtaining an average effectiveness ratio of 105%. The efforts made by the Denpasar City Revenue Agency to increase Rural and Urban Land and Building Taxes revenues are intensifying and extending. Keywords : Performance, land tax, value for money